A Peptide Inhibitor of the Human Cytomegalovirus Core Nuclear Egress Complex - Sewar Alkhashrom; Jintawee Kicuntod; Katharina Stillger; Tamara Lützenburg; Christian Anzenhofer; Ines Neundorf; Manfred Marschall; Jutta Eichler (MDPI AG, 2022)
The replication of human cytomegalovirus (HCMV) involves a process termed nuclear egress, which enables translocation of newly formed viral capsids from the nucleus into the cytoplasm. The HCMV core nuclear egress complex (core NEC), a heterodimer of viral proteins pUL50 and pUL53, is therefore considered a promising target for new antiviral drugs. We have recently shown that a 29-mer peptide presenting an N-terminal alpha-helical hook-like segment of pUL53, through which pUL53 interacts with pUL50, binds to pUL50 with high affinity, and inhibits the pUL50-pUL53 interaction in vitro. Here, we show that this peptide is also able to interfere with HCMV infection of cells, as well as with core NEC formation in HCMV-infected cells. As the target of the peptide, i.e., the pUL50-pUL53 interaction, is localized at the inner nuclear membrane of the cell, the peptide had to be equipped with translocation moieties that facilitate peptide uptake into the cell and the nucleus, respectively. For the resulting fusion peptide (NLS-CPP-Hook), specific cellular and nuclear uptake into HFF cells, as well as inhibition of infection with HCMV, could be demonstrated, further substantiating the HCMV core NEC as a potential antiviral target.